If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (m + -2) = 5 Reorder the terms: (-2 + m) = 5 Remove parenthesis around (-2 + m) -2 + m = 5 Solving -2 + m = 5 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + m = 5 + 2 Combine like terms: -2 + 2 = 0 0 + m = 5 + 2 m = 5 + 2 Combine like terms: 5 + 2 = 7 m = 7 Simplifying m = 7
| 3y-12x+6=o | | 25x-4=3x^2+8x+16 | | -1x+-5=25 | | -7-k=7-3k | | 3y=6+6x | | 16+6=x-70 | | 12-3y=14 | | -294-(-70)= | | 10x+70+7x=13+x | | (m-7)=49 | | -1+-5=25 | | -4y+4(4y+4)=8+6(8-y) | | 12x-69=3x+102 | | -.666x(6-3z-7)= | | 23x-3y=5 | | 7-2(x-3)=5-8 | | -1-5=25 | | 6=-32 | | 7(3x-9)=11(4x+7) | | 11x-77=2x+175 | | 16+6=70-x | | 6x+7-2x=4(x+3) | | 2a^2-242=0 | | 7(x+6)-8=5(x-1) | | 22-4(-6.3)=12(-6.3)+126 | | (b+c-1)6= | | 2(-7x+6)-6x=-6 | | x^2+6x-188=0 | | x^2+6x-1880=0 | | y-3=7(x-1) | | -5x-8+4x=-6x-2 | | 25m^2+80m+64= |